Buffalo Selection in Bali Province, Indonesia: Performance and Quantitative Trait Analysis - Warmadewi, Dewi Ayu; Yundari Melati, Ni Putu; Gde Bidura, I Gusti Nyoman; Sampurna, I Putu (Journal of Buffalo Science, 2024)
Background: The selection program is one of the efforts that can be made to select livestock as superior breed stock. The selection program can be carried out by looking at the performance of quantitative traits in buffalo by measuring several economically valuable traits referring to the Indonesian National Standard (SNI 7706.1: 2011) regarding superior young bull buffalo breeds. Methods: The research was carried out by directly measuring the performance of quantitative characteristics of buffalo in three regencies out of nine regencies in Bali Province, Indonesia, namely: Jembrana Regency, Tabanan Regency, and Buleleng Regency. Data analysis was carried out descriptively to obtain average quantitative characteristics and calculate the magnitude of population diversity. Results: The results obtained were that the performance of quantitative traits in male and female buffalo in Bali Province, Indonesia, was higher than the Indonesian National Standard (SNI 7706.1: 2011) regarding superior young bull buffalo breeds. The population diversity of quantitative characteristics of male buffalo aged 2-3 years old in Bali province is categorized as diverse (varied). On the other hand, male buffalo aged >3 years are in the uniform (homogeneous) category, as are female buffalo aged 2-3 years and >3 years. Conclusion: The buffalo in the province of Bali, Indonesia, were suitable for use as a breed, and effective selection was carried out on the male buffalo population aged 2-3 years. Suggestions require efforts to increase public interest in keeping buffaloes by providing protection and appreciation to breeders who want to keep buffaloes, especially female buffaloes.